Semantic Data Sharing and Pricing in Web 3.0 Using Blockchain - Sitharamulu, V.; Reddy, G. Sucharitha; Gole, Srihari Babu; Battu, Hanumantha Rao; Osman, Onur; Rasheed, Jawad; Rasheed, Jawad (Springer Science and Business Media B.V., 2025)
Web 3.0 represents an advanced internet framework that combines technologies such as blockchain and semantic communication to enable decentralized, transparent data exchange. While semantic communication reduces redundancy by transmitting contextual meaning rather than raw data and existing systems lack a cohesive integration strategy, further, the centralized models struggle with efficient semantic sharing and valuation. The work proposed integration framework of semantic web communication with blockchain to enhance reliable web 3.0 data sharing. A novel “Proof of Semantic” mechanism tackles data integrity issues, ensuring only high-quality semantic inputs. The approach also elucidates the implementation of the bottleneck method and state channels. The computational load is optimized using a semantic shared protocol across the web. Further, a hierarchical Stackelberg game model optimizes semantic pricing, balancing stakeholder incentives. Evaluations confirm the framework’s efficacy, achieving reduction in network load without compromising accuracy compared to conventional approaches.
Keywords: Web 3.0; Blockchain integration; Semantic communication; Decentralized data sharing; Incentive mechanisms